Relationship between body image and breakfast on nutritional status - Nur Husnul Khatimah; Alkhair; Dea Zara Avila (Institute of Computer Science (IOCS), 2023)
Each individual has a different perception of himself, positive or negative perception that has an impact on nutritional status. If an individual experiences self-doubt regarding his body shape negatively, he will go on a diet to get the body shape he wants. The purpose of this study was to determine the relationship between body image and breakfast behavior on the nutritional status of students of the Nutrition Study Program at Muhammadiyah University of Bima in 2022. This type of research was a correlation study with a cross-sectional approach. Respondents to this study were all 70 students of the Nutrition Study Program, Faculty of Health, Muhammadiyah University of Bima. Body image data was taken using the Body Shape Questionnaire (BSQ) questionnaire, eating behavior data was taken using the Adolescent Food Habits Checklist (AFHC ) questionnaire, student nutritional status data was taken using body index per age (b/u) based on data on weight, height body, and age of the student. The data analysis used was univariate analysis which was used to determine the description of each variable and bivariate analysis was used to determine the relationship between variables with the Spearman test. The results showed that there was a relationship between body image and nutritional status (p-value = 0.000), and there was a relationship between eating behavior and nutritional status (p-value = 0.040).